2014
DOI: 10.1097/med.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Relapse following antithyroid drug therapy for Graves’ hyperthyroidism

Abstract: Prolonged low-dose ATD therapy may be feasible in patients with high risk of relapse, such as children and patients with active Graves' orbitopathy, and in patients with previous relapse who prefer such therapy rather than surgery or radioiodine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 48 publications
0
34
1
2
Order By: Relevance
“…In contrast to our previous report concerning the risk of relapse after the first course of treatment (36), we observed no independent effect on long-term remission rate of age, ethnicity or serum TRAb levels at diagnosis (40). Other factors, such as sex, iodine intake, smoking and genetic background are thought to modulate individual responsiveness in adults (44,48). This study was subjected to several limitations: a relatively small number of boys were included, possibly preventing the detection of male sex as a determinant of GD relapse, a lack of serum TRAb determinations during the follow-up and a lack of information about genetic background, precluding evaluations of the association of these factors with relapse rate (37).…”
Section: Recent Findings From Studies In Childrencontrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast to our previous report concerning the risk of relapse after the first course of treatment (36), we observed no independent effect on long-term remission rate of age, ethnicity or serum TRAb levels at diagnosis (40). Other factors, such as sex, iodine intake, smoking and genetic background are thought to modulate individual responsiveness in adults (44,48). This study was subjected to several limitations: a relatively small number of boys were included, possibly preventing the detection of male sex as a determinant of GD relapse, a lack of serum TRAb determinations during the follow-up and a lack of information about genetic background, precluding evaluations of the association of these factors with relapse rate (37).…”
Section: Recent Findings From Studies In Childrencontrasting
confidence: 56%
“…Remission rates vary between geographic areas and seem to be better in Europe and in Japan than those in the USA, where RAI was, until recently, favored as the first-line treatment or used within 1 year of the start of the ATD treatment (12,42,43). Lower remission rates have been reported for men, smokers (especially men) and those with severe biochemical disease with high serum TRAb levels and large goiters (≥80 g) (12,44). However, some patients prefer to prolong treatment with low doses of ATD (2.5-7.5 mg/day, MMI or CMZ) over several years (45) and two recent studies have even suggested that prolonged ATD treatment yielded better results (46,47).…”
Section: Recent Findings From Adult Studiesmentioning
confidence: 99%
“…4). In a subset of women becoming pregnant while treated with ATD for GD, the risk of hyperthyroidism relapse will be unacceptably high if ATD is withdrawn (75). This will be women who started ATD therapy recently (<6 months), who still have suppressed TSH, who have a relatively high serum T 3 (76), high levels of TRAb, large goitre, active orbitopathy, or other signs of active disease.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…RAI should be considered if ATDs are not tolerated, in case of relapse and in patients with cardiac disease [4,114,115,116,117,118] (1/+00).…”
Section: Treatment Of Endo Shyper: Effects Of Treatment With Atds Andmentioning
confidence: 99%